PENGARUH KOMPETENSI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI PADA KOPPAS SRINADI UNIT PERCETAKAN DAN KONVEKSI - Ni Kadek Indah Krisnayanti; Anak Agung Dwi Widyani; Tiara Carina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
Employee performance is the result of employee work both in terms of quality and quantity in carrying out the duties and responsibilities assigned to the employee. To improve employee performance, it is necessary to have high competency and good work motivation so that employees are increasingly encouraged to carry out their duties so that they can increase their overall productivity. This research aims to obtain empirical evidence of the influence of competence on employee performance with work motivation as a mediating variable at KOPPAS Srinadi Printing and Convection Unit. The population and sample in this research were all employees at KOPPAS Srinadi Divorce and Convection Unit, totaling 31 employees. Data collection in this research used a questionnaire. The data analysis technique uses SEM-PLS version 3.0. The research results show that competence has a positive and significant effect on employee performance and work motivation, work motivation has a positive and significant effect on employee performance, work motivation is able to mediate the effect of competence on employee performance.